2020
DOI: 10.1155/2020/4356386
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress-Mediated Blood-Brain Barrier (BBB) Disruption in Neurological Diseases

Abstract: The blood-brain barrier (BBB), as a crucial gate of brain-blood molecular exchange, is involved in the pathogenesis of multiple neurological diseases. Oxidative stress is caused by an imbalance between the production of reactive oxygen species (ROS) and the scavenger system. Since oxidative stress plays a significant role in the production and maintenance of the BBB, the cerebrovascular system is especially vulnerable to it. The pathways that initiate BBB dysfunction include, but are not limited to, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 358 publications
(310 reference statements)
0
52
0
Order By: Relevance
“…Along with that, the present study demonstrated a possible neuroprotective effect of CeNPs through its antioxidant activity. Because of its reported ability to pass the blood-brain barrier (BBB) making it a suitable prospect for the neural diseases' treatment (Rzigalinski et al, 2017;Song et al, 2020) in the case of FIP intoxicated rats. Also, CeNPs showed increased activity of antioxidant enzymes (SOD and GPx) with lower levels of the biomarkers of lipid peroxidation (MDA and NO).…”
Section: Discussionmentioning
confidence: 99%
“…Along with that, the present study demonstrated a possible neuroprotective effect of CeNPs through its antioxidant activity. Because of its reported ability to pass the blood-brain barrier (BBB) making it a suitable prospect for the neural diseases' treatment (Rzigalinski et al, 2017;Song et al, 2020) in the case of FIP intoxicated rats. Also, CeNPs showed increased activity of antioxidant enzymes (SOD and GPx) with lower levels of the biomarkers of lipid peroxidation (MDA and NO).…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory and reactive oxygen species (ROS) secreted by immune cells such as neutrophils and monocytes/macrophages are considered central factors of TJ disruption and BBB leakage following oxidative stress-induced injuries [ 107 ]. Therefore, the antioxidant effects of MSC therapy, reported in various investigations, might be a potential strategy for endothelium barrier restoration.…”
Section: Potential Mechanisms Of Blood–brain Barrier Preservation By Mscs Following Ischemiamentioning
confidence: 99%
“…The effects of ROS action include excessive lipid peroxidation, altered function of receptors, ion channels, and other membrane proteins, which impair cell membrane fluidity and permeability [ 33 35 ]. Ischemic brain injury also disturbs the blood-brain barrier (BBB) leading to leukocyte infiltration and edema [ 36 , 37 ]. Under these conditions, inflammatory reactions are intensified [ 38 , 39 ].…”
Section: Oxidative Stress Inflammation and Strokementioning
confidence: 99%